PROTECTION OF THE RIGHT TO SECURITY FOR MANGROVE BEACH TOURISTS - Maulana, Andrian; Hasanah, Uswatun (TRUNOJOYO LAW REVIEW, 2023)
This study aims to examine whether selfies on bridges in mangrove beach tourist destinations can be qualified as high-risk tourism activities and how the law provides protection for tourists who jump from bridges in mangrove beach tourist destinations. This type of research includes normative legal research, using a statutory approach. Primary legal material and secondary legal material obtained are then analyzed using deductive-inductive logic and analyzed using teleological interpretation. The results of the study show that taking selfies on bridges in mangrove beach tourist destinations does not qualify as high-risk tourism, while legal protection for tourists who jump on bridges in mangrove beach tourist destinations, even if they do not get insurance. However, the tourism manager is responsible for negligence in providing the comfort and safety of tourists, as stipulated in Article 26 Letter (d) of the Tourism Law and is obliged to provide compensation, as stipulated in Article 4 letter (h) UUPK and Article 1365 of the Civil Code.